Mine Seismology: Seismic Warning Concept Case Study from Vaal Reefs Gold Mine, South Africa - Glazer, S.N (Springer International Publishing, 2018)
This book illustrates how mine seismology can be used to improve underground safety standards. It describes several preventive actions that have been put into practice at the 5B Area of No. 5 Shaft Vaal Reefs gold mine after issuing seismic warnings. These included additional safety pillars, changes in mining sequences and directions, and a review of the mining strategy for the entire 5B area. The presented experiment with seismic warning concept was a success because it was an internal mine project. Further, the Vaal Reefs management adopted the philosophy that the success rate should be measured in the preventive actions taken, not in the success of the prediction itself. Reviewing these and other aspects, the book clearly demonstrates how mine seismology can effectively improve underground safety standards. Stefan Glazer's book (...) addresses in a very comprehensive manner both technical and practical proble ms of implementing and then effectively using microseismic networks and data. (...) Stefan proves that through comprehensive microseismic data analysis the location of potential rock burst can be assessed and then prevention action plans can be developed, providing more confidence to management and workers that deposit[s] can be mine[d] safely. Michal Stawski, VP Strategic Geomechanical Specialist, PT Freeport Indonesia I began reading this story expecting to find a technical review of the science of seismology and its application in mining, [but] this book is much more than that. (...) This is a must-read for those managing seismically active mines and should provide a wake-up call to the industry as the complex morality surrounding the management of seismic risk needs to be clarified in order for this to advance. Eric Strom, Director Underground Mining, New Gold Inc. As a mining geotechnical practitioner having experience in large open pit and underground massive mining operations, I have learned that mining induced seismicity can have a significant impact on the safety and economics of operations. However, seismicity is a complex field that is generally left to specialists with little input from geotechnical engineers and engineering geologists. (...) This is a must read for mine seismologists, geotechnical practitioners and mining engineers alike, and will be a welcome and much needed addition to my own book cabinet. This will be [an] invaluable work as our industry progresses to the mining of new depths in both the underground and open pit environments. Desmond Mossop Pr.Sci.Nat., Principal Engineering Geologist, SRK Consulting.